A DETERMINANTS OF DIVIDEND POLICY: EMPIRICAL EVIDENCE FROM INDONESIAN PUBLICLY LISTED COMPANIES - Theresia Trisanti; Algifari Algifari; Astuti Purnamawati; Conny Tjandra Rahardja (Kajian Ekonomi dan Bisnis, 2026)
This study examines the determinants of dividend policy among Indonesian listed manufacturing firms. Specifically, it investigates the effects of sales, profitability, leverage, and asset growth on dividend payout ratio. The study employs secondary data obtained from 80 manufacturing firms listed on the Indonesia Stock Exchange during the 2023–2025 period, resulting in 320 firm-year observations. Multiple regression analysis is used to test the proposed hypotheses. The findings reveal that sales and profitability have a positive and significant effect on dividend payout, indicating that firms with stronger financial performance tend to distribute higher dividends to shareholders. In contrast, asset growth has a negative and significant effect, suggesting that firms with higher growth opportunities prefer to retain earnings for expansion. Meanwhile, leverage shows a negative but statistically insignificant relationship with dividend payout. Overall, the results highlight the trade-off between growth opportunities and dividend distribution decisions in emerging market contexts.